Development Of Ultra High Frequency Energy Harvester Using Circular Spiral Array With Corporate Feeding - Kang, Chia Chao (2016)
This thesis is to design an alternative antenna structure that will increase gain of the antenna, the amount of harvested energy and provide high power during rectification. The research works generate a steady output at a frequency of 956 MHz for RF energy harvesting system. The design of the circular spiral antenna is performed using Computer Simulation Technology (CST) and Advanced Designed System (ADS). The circular spiral antenna is integrated with the rectifying circuit to efficiently convert the input RF signal from alternating current (AC) to direct current (DC). Three configurations of the antenna designs were proposed namely single circular spiral antenna, 1x2 circular spiral antenna and 2x4 circular spiral antenna. The proposed antenna that had been developed is based on the basic antenna characteristic such as return loss, radiation pattern and gain. The 1x2 array antennas and 2x4 array antenna were designed using the corporate feed method that will increase the gain and enhanced the RF harvesting output voltage. The rectification of RF to DC energy used zero bias schottky diode that convert the incoming harvested energy. The results show that all the three design posses gain of 2.3 dBi, 3.2 dBi and 5 dBi, while the output voltage generated were 17 mV, 59.4 mV and 79 mV respectively. It is found also that the circular spiral antenna can provide a constant output DC voltage which is useful for UHF application.